Cournot competition with heterogenous firms, welfare and misallocation - Enrico De Monte; Bertrand M. Koebel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
This paper characterizes the short- and long-run Cournot equilibrium with heterogeneous firms and stochastic technological change. In our model, firms have different technologies with heterogeneous fixed and variable costs and various degrees of markups. In a framework with homogeneous firms, Mankiw and Whinston (1986) show that the long-run Cournot equilibrium may be inefficient due to too many entries. We extend their result to the case of heterogeneous firms and show that higher industrial concentration of production is welfare improving. Using administrative data for French manufacturing firms, we estimate a wide degree of unobserved heterogeneity in both fixed and variable costs, and find a negative correlation between both. Our simulation results show that markups surprisingly only induce slight inefficiencies in the allocation of output, implying that it is almost compatible with welfare maximisation. Instead, firms' choice to employ heterogeneous and often inefficient technologies turns out to harm more substantially welfare and aggregate output.
Keywords: C33; L11; L60; 330; cost function; fixed cost; marginal cost; returns to scale; technological change; misallocation; markups; nonlinear least squares; panel data